2013
DOI: 10.1002/hipo.22216
|View full text |Cite
|
Sign up to set email alerts
|

Depressive mood modulates the anterior lateral CA1 and DG/CA3 during a pattern separation task in cognitively intact individuals: A functional MRI study

Abstract: Although patients with major depressive disorder typically have a reduced hippocampal volume, particularly in the cornu ammonis 1 (CA1), animal studies suggest that depressive mood is related to the dentate gyrus (DG). In this study, our objective was to clarify which hippocampal subregions are functionally associated with depressive mood in humans. We conducted a functional MRI (fMRI) study on 27 cognitively intact volunteers. Subjects performed a modified version of a delayed matching-to-sample task in an MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…Within the hippocampal formation, DG-CA3 volume is decreased in individuals with early life stress history (Teicher et al, 2012) and in PTSD . A recent study found impaired pattern separation in the DG of individuals with elevated depression scores (Fujii et al, 2014). Although it is not clear if stress contributes to the higher depression scores (or depressed mood) in these individuals, these observations suggest, albeit indirectly, that stress alters pattern separation in the DG-CA3 circuit.…”
Section: Stress Confers Vulnerability To Overgeneralization Of Fear Tmentioning
confidence: 97%
“…Within the hippocampal formation, DG-CA3 volume is decreased in individuals with early life stress history (Teicher et al, 2012) and in PTSD . A recent study found impaired pattern separation in the DG of individuals with elevated depression scores (Fujii et al, 2014). Although it is not clear if stress contributes to the higher depression scores (or depressed mood) in these individuals, these observations suggest, albeit indirectly, that stress alters pattern separation in the DG-CA3 circuit.…”
Section: Stress Confers Vulnerability To Overgeneralization Of Fear Tmentioning
confidence: 97%
“…This behavioral difference is accompanied by increased amygdala activity and decreased DG/CA3 activity in high-resolution fMRI. Furthermore, the level of DG/CA3 activity is negatively correlated with depressive symptom severity, which indicates that reduced DG/CA3 activity may be a pathological condition 51,113 . Older adults experiencing late-life depression also show enhanced discrimination of negative scenes, in addition to alterations in their amygdala–entorhinal–hippocampal network 114 (Fig.…”
Section: Neuropsychiatric Diseasementioning
confidence: 99%
“…Moreover, in mice this task is critically dependent on adult hippocampal neurogenesis (reviewed in Aimone, Deng, & Gage, 2011; Clelland et al, 2009). Importantly, defects in pattern separation of emotionally relevant stimuli have emerged as a cognitive phenotype of MDD (Fujii et al, 2014; Leal, Tighe, Jones, & Yassa, 2014). In the context of anxiety disorders defects in pattern separation have been proposed to underlie the commonly observed phenomenon of stimulus generalization (Kheirbek, Klemenhagen, Sahay, & Hen, 2012).…”
Section: The Gabaergic Deficit Hypothesis Of Mddmentioning
confidence: 99%
“…Moreover, disinhibition of HPA axis function correlates with depressive-like increases in emotional reactivity of mice with impaired hippocampal neurogenesis (Shen et al, 2010; Snyder et al, 2011). Although several studies have reported normal emotional behavior following ablation of hippocampal neurogenesis in mice (reviewed in Petrik, Lagace, & Eisch, 2012), hippocampal neurogenesis is also essential for hippocampus-dependent pattern separation, a cognitive task that is impaired in MDD (Fujii et al, 2014; Leal et al, 2014). …”
Section: Gabaergic Transmission In Relation To Stress-based Etiolomentioning
confidence: 99%
See 1 more Smart Citation